FUNDAMENTAL PRINCIPLES OF TRANSFORMATIONS OF SOCIO-PSYCHOLOGICAL PRACTICES OF MARRIAGE AND FAMILY PARTNERSHIP AND PATERNITY - Yatsyna, Olena (PSYCHOLOGICAL JOURNAL, 2018)
On the example of marriage and family practices as products of constructing the reality of a certain cultural-historical space reveals the psycho-historical reconstruction of the family, marriage and paternity. It is noted that the social content of the family, which is inscribed in the framework of the disposition of nepotism, indicated its socialization by the state, where regulation is carried out using the system of roles, norms, structural and functional organization of marriage and family practices and control over sexuality. The processes of industrialization, the sexual revolution and women's emancipation have become a catalyst for changes in the views on marriage, family and paternity. According to the author, the liberalization of sexual relations in the context of the historical events of that time is aimed at destroying the “bourgeois” family as a social unit and egalitarian experiments: communes, free love and legitimizing the practices of the mono-mother family. It is noted that sexual relations without intent to continue another kind of connections - marriage and procreation - paternity found the instability of the matrix "disposition of family", which are considered as the beginning of the process of its deconstruction. The delimitation of sexual relations from reproductive function left the practice of sexual partnership outside the disposition of nepotism, thus laying new rules of behavioral culture in the sphere of marriage and family relations. It is concluded that the disposition of nepotism as a matrix of changes in the practices of family, marriage and paternity cultivated by society, in a different social environment, is changing. The functioning of the practices of civil partnership and mono-mother families led to a break in relations: sexuality - reproduction and marriage - paternity, which are considered as signals of institutional transformations of the family, marriage and fatherhood. The delimitation of sexual practices from the disposition of the family in a historical perspective allowed the construction of configurations where the bond breaks: sex - gender not only diversified the functional-role relationships of men / women, but also indicated the depth of changes in the institutions of family, marriage and paternity.